EVALUASI KETEBALAN PERKERASAN KAKU (RIGID PAVEMENT) PADA RUAS JALAN KALIGAWE RAYA KM 5+500 – 6+700 BERDASARKAN METODE MANUAL DESAIN PERKERASAN (MDP) 2024 - Achmad Himawan; Rachmat Mudiyono (Pondasi, 2025)
The Kaligawe Raya road section in the Pantura corridor at KM 5+500–6+700 in Semarang City supports heavy vehicle traffic and national logistics. The 2017 Pavement Design Manual was used to construct a rigid pavement for this segment in 2023. The 2024 Pavement Design Manual (MDP 2024), which uses an empirical-mechanistic approach, requires a reevaluation of the existing concrete slab thickness to determine its compliance with the updated standards and its ability to withstand projected traffic loads over the design life. This study uses a quantitative case study. Field surveys of pavement and structural conditions provide primary data, while ADT, vehicle mix, and technical papers provide secondary data. Based on the technical data, the pavement thicknesses of the 2017 MDP and 2024 MDP are compared. Due to frequent loading, fatigue, and erosion, the 2024 MDP recommends a thicker slab of 6.5 cm. The older method may lead to design life discrepancies. MDP 2024 better predicts pavement performance for future traffic.